SISTEM REKOMENDASI DALAM MENENTUKAN KAYU TERBAIK UNTUK BAHAN GITAR DENGAN MENGGUNAKAN METODE WASPAS - Tundo Mujahid (Journal of Data Science Theory and Application, 2022)
This research occurred because there were complaints from consumers against one of the guitar shops located in Dongkelan, Krapyak, Yogyakarta with the condition of the guitar that was purchased quickly weathered and dull in terms of color. Based on these problems, the solution is to use the Weighted Aggregated Sum Product Assessment (WASPAS) Decision Support method which is assisted by experts in determining the right criteria related to the best in making guitar materials, after calculating the exact results based on the problem, in the form of wood strength criteria, wood grain, texture, and wood weight. All these criteria are then managed using WASPAS, with the data used as many as 28 types of wood data, which were obtained from craftsmen in the area. After obtaining the results, 3 woods that are suitable for use as guitar making materials in sequence are Bubinga wood with a value of 6.38884, Ebony wood with a value of 5.98133, and Bocote wood with a value of 5.98133 from several alternative wood choices. Proving the results of the WASPAS method, the respondents carried out directly by providing the results of the method to guitar makers. Of the 17 expert guitar makers, 15 said they agreed with the top 3 rankings, and 2 said they did not agree. So that the level of assessment based on the assessment is 88.24%